The Antimicrobial Photodynamic Therapy in the Treatment of Peri-Implantitis. (26th June 2016) - Romeo, Umberto; Nardi, Gianna Maria; Libotte, Fabrizio; Sabatini, Silvia; Palaia, Gaspare; Grassi, Felice Roberto
Abstract : Introduction . The aim of this study is to demonstrate the effectiveness of addition of the antimicrobial photodynamic therapy to the conventional approach in the treatment of peri-implantitis. Materials and Methods . Forty patients were randomly assigned to test or control groups. Patients were assessed at baseline and at six (T1), twelve (T2), and twenty-four (T3) weeks recording plaque index (PlI), probing pocket depth (PPD), and bleeding on probing (BOP); control group received conventional periodontal therapy, while test group received photodynamic therapy in addition to it. Result . Test group showed a 70% reduction in the plaque index values and a 60% reduction in PD values compared to the baseline. BOP and suppuration were not detectable. Control group showed a significative reduction in plaque index and PD. Discussion . Laser therapy has some advantages in comparison to traditional therapy, with faster and greater healing of the wound. Conclusion . Test group showed after 24 weeks a better value in terms of PPD, BOP, and PlI, with an average pocket depth value of 2 mm, if compared with control group (3 mm). Our results suggest that antimicrobial photodynamic therapy with diode laser and phenothiazine chloride represents a reliable adjunctive treatment to conventional therapy. Photodynamic therapy should, however, be considered a coadjuvant in the treatment of peri-implantitis associated with mechanical (scaling) and surgical (grafts) treatments.